The spread of Zika and the potential for global arbovirus syndemics. Issue 1 (2nd January 2017) - Singer, Merrill
ABSTRACT: It is estimated that over a million people die each year from infectious diseases of zoonotic origin and hundreds of millions suffer from these pervasive threats to human well-being. In light of the emergent global concern over the Zika virus, evidence that it has not one but two competent mosquito vector species in the Aedes family, and that both can be co-infected with other pathogens including dengue and chikungunya, this paper examines research suggesting the prospect of significant twenty-first-century outbreaks of arbovirus syndemics. Uniting the concepts 'synergy' with 'epidemic', a syndemics approach recognises that diseases in a population occur neither independent of social and ecological conditions, nor in isolation from other diseases. Assessment of the potential for arbovirus syndemics entails a review of the human role in the global spread of Aedes mosquitoes, the socio-environmental conditions of Aedes diffusion, the increasing likelihood of co-transmission of arbovirus diseases, evidence of co-infection and concern about the adverse health effects of arbovirus syndemic interaction, and the need for an appropriate environment-sensitive framework for effective public health responses. Called Planetary Health, this emergent framework confronts conceptual, knowledge, and governance challenges created by the dramatic shifts in environments, climates, people, vectors, and pathogens in the world.